Kajian Aspek Pidana Kepemilikan Kartu Tanda Penduduk (KTP) Indonesia Secara Ilegal Oleh Warga Negara Asing - Mardiah, Ainun; Adam, Sherly; Patty, Jetty Martje (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2023)
Introduction: Illegal possession of Indonesian identity cards (KTP) by foreign nationals (WNA) is still a problem that often occurs in the community. The requirement for a foreigner to have an Indonesian KTP is legally regulated in Law Number 24 of 2013 concerning amendments to Law Number 23 of 2006 concerning population administration. So whether the ownership of Indonesian KTP by foreigners has fulfilled the requirements of the provisions stipulated in the law.Purposes of the Research:  The purpose of the study is to examine the criminal aspects of illegal ownership of Indonesian KTPs by foreigners and discuss the legal consequences. Methods of the Research: The method used in this study is normative juridical with a statutory approach, a concept approach, and a case approach. Legal material collection techniques use literature studies and legal material processing and analysis techniques using qualitative methods.Results of the Research: The results of the study show that the criminal aspects of illegal ownership of KTP by foreigners include the criminal act of forgery which in this case the ownership is invalid or inkrah because it does not meet the requirements for ownership of an Indonesian KTP that has been regulated in Indonesian laws and regulations.In the case of having an ID card illegally so that it causes the ID card to be a fake letter, the act of forgery has its own responsibility for the criminal acts that have been committed by the perpetrator.The legal consequences of illegal possession of Indonesian KTPs by foreigners can be processed legally and subject to article 263 of the Criminal Code because the ownership of the KTP is not found in accordance with article 63 of the Population Administration Law so that the KTP is fake or legally invalid. When making an ID card, the perpetrator involves civil servants, population and civil registration and bribes to issue the ID card so that based on article 55 paragraph (1) of the Criminal Code, the perpetrator can be subject to article 5 paragraph (1) of the Criminal Law to be held accountable for criminal acts that have been committed by the perpetrators